Incentive alignment in ecosystems: The role of complementarity types and multi‐sided bargaining - Chatain, Olivier; Plaksenkova, Elena (Strategic Management Journal, 2025)
Abstract Research Summary Alignment of incentives to improve value creation in ecosystems is crucial to their growth and survival. We examine how two fundamental ecosystem features affect alignment: types of complementarities and their interplay with multi‐sided bargaining over value. Using a formal model, we find that multi‐sided bargaining typically causes misalignment, in patterns that vary dramatically depending on the type of complementarities. For instance, we find that multiplicative complementarities typically entail weak alignment among participants. In contrast, when value creation is constrained by the weakest component, alignment can be alternatively very strong or very weak. We also find that the starting levels of participants' functionality matter. This suggests new avenues for assessing ecosystem performance and the potential for alignment among participants. Managerial Summary Managers of firms operating in ecosystems need to understand the factors that make their partners aligned with the objective of increasing the ecosystem's value creation. Our research shows that, under multi‐sided bargaining, a major driver of incentive alignment is the type of complementarity between ecosystem's components, that is, how the different pieces of the ecosystem contribute to value creation. Depending on the complementarity type (multiplicative, additive, and weakest‐link), and ecosystem partners' starting levels of functionalities, we show which combinations are intrinsically favorable for aligning development incentives and which ones may undermine alignment. These findings can serve as a guide to diagnose the potential for misalignment among ecosystem partners and how much value creation is at stake.